Amending charge separation and migration in TiO2 nanosheet via Au nanoparticles ensemble and its synergy in photoelectrocatalytic methanol oxidation. (15th April 2022) - Praveen, R.; Murugan, C.; Pandikumar, A.; Ramaraj, R.
Abstract: In this report, the preparation of an ensemble of hydrothermally synthesized TiO2 nanosheets with Au nanoparticles (TiO2 NSs-Au NPs) and their photoelectrocatalytic methanol oxidation behavior are accounted. The absorption spectral studies confirmed the successful emergence of Au NPs on TiO2 NSs ensemble and the existence of Au NPs broadened the light absorption to the visible light spectrum. The crystalline and structural complexity analysis confirms the anatase TiO2 as a major product in this synthesis. Morphology studies revealed the formation of 2 dimensional TiO2 NSs with chemically deposited Au NPs at the TiO2 surface and it was further confirmed by STEM-HAADF-EDS mapping studies. The ITO/TiO2 NSs-Au modified photoelectrode showed a synergistic catalytic response towards photoelectrocatalytic methanol oxidation than the ITO/TiO2 NSs electrode. Among them, TiO2 NSs with 1 mM Au NPs deposited composite (TiO2 NSs-Au (1)) showed 2-fold higher photocurrent for methanol oxidation than their pristine TiO2 NSs. The deposited of Au NPs in TiO2 NSs-Au nanocomposites facilitates the photoinduced charge separation and charge migration processes. Coherently the charge recombination process diminished in the TiO2 NSs-Au nanocomposite materials. The best synergistic photoelectrocatalytic methanol oxidation reaction at the ITO/TiO2 NSs-Au (1) modified electrode was achieved via extended visible light absorption with Schottky barrier induced enhancement of interfacial electron transfer process. Highlights: Two-dimensional TiO2 nanosheets modified with Au NPs (TiO2 NSs-Au). The ITO/TiO2 NSs-Au modified electrodes show a synergistic catalytic response. ITO/TiO2 NSs-Au shows enhanced photoelectrocatalytic methanol oxidation. The Schottky barrier enhances the interfacial electron transfer process.